Combinatorial study of thermal stability in ternary nanocrystalline alloys. (15th April 2020) - Kube, Sebastian A.; Xing, Wenting; Kalidindi, Arvind; Sohn, Sungwoo; Datye, Amit; Amram, Dor; Schuh, Christopher A.; Schroers, Jan
Abstract: Nanocrystalline alloys can be stabilized through selective grain boundary segregation of specific solute element additions. Increasing attention is being paid to ternary and higher order systems, where complex interactions govern segregation. To efficiently study the large composition spaces of such systems, we apply a high-throughput combinatorial technique revealing nanocrystalline stability through composition-grain-size maps. We compare two systems with distinct binary and ternary alloy interactions: In Pt–AuAg both binaries are expected to be stable, whereas in Pt–AuPd the Pt–Pd binary is unstable and Au-induced co-segregation of Pd was previously reported. For ternary Pt–AuAg we find excellent thermal stability throughout. The Pt–AuPd system, by contrast, divides into an unstable regime, where Pd solute dominates and precipitates, and a stable regime, where Au solute dominates and retains Pd in the grain boundary. Overall, by combining current theory and the introduced combinatorial approach, stable multicomponent nanocrystalline composition spaces can be rapidly determined. Graphical abstract: Image, graphical abstract